2016
DOI: 10.1002/14651858.cd012382
|View full text |Cite
|
Sign up to set email alerts
|

Non-steroidal anti-inflammatory drugs for sciatica

Abstract: This updated systematic review including 10 trials evaluating the efficacy of NSAIDs versus placebo or other drugs in people with sciatica reports low- to very low-level evidence using the GRADE criteria. The efficacy of NSAIDs for pain reduction was not significant. NSAIDs showed a better global improvement compared to placebo. These findings must be interpreted with caution, as the level of evidence according to the GRADE classification was very low for the outcome pain reduction and low for global improveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 59 publications
0
32
0
4
Order By: Relevance
“…There appears to be no difference in analgesic efficacy between different NSAIDs, or between COX-2 selective versus nonselective NSAIDs. There is mixed evidence for the use of NSAIDs in pain conditions with a predominantly neuropathic component including lumbosacral radicular pain, though these medications are often used to treat these conditions [19,20]. A Cochrane review evaluating NSAIDs for sciatica based on predominantly low-quality studies found non-significant differences between NSAIDs and placebo for pain relief, though NSAIDs were superior for global improvement [20].…”
Section: Non-steroidal Anti-inflammatory Drugsmentioning
confidence: 99%
“…There appears to be no difference in analgesic efficacy between different NSAIDs, or between COX-2 selective versus nonselective NSAIDs. There is mixed evidence for the use of NSAIDs in pain conditions with a predominantly neuropathic component including lumbosacral radicular pain, though these medications are often used to treat these conditions [19,20]. A Cochrane review evaluating NSAIDs for sciatica based on predominantly low-quality studies found non-significant differences between NSAIDs and placebo for pain relief, though NSAIDs were superior for global improvement [20].…”
Section: Non-steroidal Anti-inflammatory Drugsmentioning
confidence: 99%
“…management, large-scale clinical trials for radicular syndromes are variable. 21 Though dramatic benefit from NSAIDs is rare, patients may report some benefit. This matches the mild global improvement seen in a Cochrane meta-analysis.…”
Section: Management Of Radicular Painmentioning
confidence: 99%
“…This matches the mild global improvement seen in a Cochrane meta-analysis. 21 Short course of NSAIDs can be helpful in acute and subacute radicular pain, guarding for adverse drug reactions. In a similar fashion, shortcourse corticosteroids have mild to moderate benefit for acute and subacute radicular pain.…”
Section: Management Of Radicular Painmentioning
confidence: 99%
“…Біль є найчастішою скаргою хворих з патологією опорнорухового апарату й однією з найчастіших причин звернення по лікарську допомогу, втрати працездатності та вживання нестероїдних протизапальних препаратів (НПЗП). М'язовоскелетний біль досить часто є резистентним до лікування НПЗП [8]. Рентгенологічні, магнітно-резонансні (МРТ) та інші методи візуальної діагностики, за даними літератури, не завжди корелюють зі ступенем клінічних проявів [1,2].…”
Section: актуальністьunclassified